Bruce family papers - Bruce, Charles, 1798-1879.; Bruce, Elvira, 1788-1858.; Bruce, James, 1763-1837.
Plantation accounts of Charles Bruce and his parents, Elvira Bruce and James Bruce, of Staunton Hill Plantation, Charlotte Co., Va. Includes household accounts of Elvira Bruce following her move to Richmond, Va., and a pardon of Charles Bruce by President Andrew Johnson.
Charles Bruce: plantation owner, Virginia state senator, and Confederate Army officer; James Bruce
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Johnson, Andrew, -- 1808-1875.; Bruce family; Plantations -- Virginia -- Charlotte County; Richmond (Va.) -- History; Staunton Hill Plantation (Va.); Virginia -- Social life and customs